Composite negative electrode material and preparation method thereof, negative electrode sheet and preparation method thereof, and sodium ion battery
Patent Information
- Application Number
- CN202611324987.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0018]本发明具有以下有益效果:通过选择特定的树脂基硬碳颗粒,并在其表面通过部分中和聚丙烯酸混合物包覆层,构建了兼具近碳基体侧氢键锚固与远基体侧离子交联亲钠特性的功能梯度复合界面层。该结构在近碳基体侧主要依靠氢键实现紧密界面结合,显著增强界面机械强度;远基体侧(电解液界面侧)则以离子交联网络结构为主导,赋予界面优异的柔性缓冲性能。同时,部分中和引入的羧酸钠基团(-COONa)提供了良好的亲钠性,而硬碳表面经氧化引入的含氧官能团,既确保了对水基浆料的良好润湿性,又提供了充足位点与包覆层形成氢键锚定作用,从而协同优化极片结构稳定性和电化学相容性。在贫负极电池工作条件下,当硬碳储钠位点接近饱和状态时,界面部分中和聚丙烯酸分子中的羰基氧原子孤对电子可与电解液中的钠离子形成配位作用,均匀化离子传输位点,缓解浓差极化,这一机制显著降低了钠金属成核过电位。同时,包覆层中的离子交联网络结构能够有效缓冲电沉积过程中的体积形变,从而缓解电芯膨胀,复合功能显著提升电池的循环寿命。因此,本发明创新性地将部分中和聚丙烯酸从传统粘结剂角色拓展为多功能界面修饰层用于贫负极体系,其羧基基团不仅维持了极片结构的粘结稳定性,更重要的是实现了电解液体系中钠离子行为的精准调控。该设计有效缓解了传统硬碳负极面临的膨胀大、循环稳定性差、枝晶生长和容量快速衰减等关键科学问题,为贫负极体系下钠金属的均匀沉积提供了创新解决方案。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a composite negative electrode material and its preparation method, a negative electrode sheet and its preparation method, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries, as a novel energy storage technology, have shown broad application prospects in the field of large-scale energy storage due to their advantages such as abundant sodium resources and low cost. In recent years, lean anode design (N / P ratio much lower than 1.2 in conventional batteries) has become one of the effective ways to improve the energy density of sodium-ion batteries. This design achieves overall battery weight reduction and cost reduction by significantly reducing the amount of lean anode material. However, this extreme operating condition poses unprecedented challenges to the anode material system: with limited anode capacity, it is necessary to ensure sufficient sodium-ion storage capacity while withstanding the drastic volume changes during repeated sodium insertion and extraction processes.
[0003] Carbon-based materials, as the mainstream anode material for sodium-ion batteries, utilize two sodium storage mechanisms: defect adsorption and interlayer intercalation. Hard carbon, due to its unique disordered layer structure and nanopores, exhibits high reversible specific capacity (typically exceeding 300 mAh / g) and excellent rate performance. However, in practical applications, the abundant oxygen-containing functional groups and structural defects on the surface of hard carbon generally result in an initial coulombic efficiency below 80%, leading to irreversible consumption of active sodium ions. More critically, under lean anode conditions, the local current density on the anode increases significantly, triggering uneven sodium deposition / dissolution and exacerbating the volume expansion of hard carbon particles (up to 120% or more of their original volume). This expansion stress disrupts the electrode's bonding network, causing the active material to peel off from the current collector, while simultaneously exposing new carbon surfaces that trigger continuous electrolyte decomposition, ultimately resulting in rapid capacity decay and a continuous increase in interfacial impedance.
[0004] In existing technologies, strategies to improve the performance of carbon anodes mainly include high-temperature graphitization to reduce surface defects and asphalt coating to reduce interfacial reactivity. However, these methods either sacrifice the sodium storage capacity of the material or are difficult to adapt to aqueous slurry systems. Regarding binders, while traditional sodium carboxymethyl cellulose (CMC) can provide basic bonding strength, its linear molecular structure has limited adaptability to volumetric stress, making it prone to electrode cracking during lean anode cycling. Oily binders such as polyvinylidene fluoride (PVDF), while elastic, require the use of toxic solvents and have insufficient interfacial bonding strength with hard carbon. These technological bottlenecks severely restrict the practical application of lean anode sodium-ion batteries.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a composite negative electrode material and its preparation method, a negative electrode sheet and its preparation method, and a sodium-ion battery to improve the above-mentioned technical problems.
[0007] This invention is implemented as follows: In a first aspect, the present invention provides a composite negative electrode material comprising a hard carbon matrix and a partially neutralized polyacrylic acid mixture coating layer covering the surface of the hard carbon matrix. The partially neutralized polyacrylic acid mixture coating layer is a functional composite layer, which mainly functions as hydrogen bond anchoring on the side close to the hard carbon matrix and mainly functions as sodium-loving ion crosslinking network on the side away from the hard carbon matrix. The hard carbon matrix is a self-exothermic resin-based hard carbon particle.
[0008] In an optional embodiment, the precursor of the self-exothermic resin-based hard carbon particles is a self-exothermic resin whose molecular chain carries at least one functional group selected from hydroxyl, carboxyl, cyano, and hydroxymethyl groups. The self-exothermic resin can undergo a condensation crosslinking exothermic reaction during pyrolysis. Preferably, the surface oxygen-containing functional group content of the self-exothermic resin-based hard carbon particles is 2~5 at.%, and the specific surface area is 100~250 m² / g.
[0009] In an optional embodiment, the degree of neutralization of the partially neutralized polyacrylic acid mixture forming the partially neutralized polyacrylic acid mixture coating layer is 30-70%. The degree of neutralization refers to the molar percentage of carboxyl groups (-COOH) on the polyacrylic acid molecular chain that are neutralized to sodium carboxylate groups (-COONa).
[0010] In an optional embodiment, the partially neutralized polyacrylic acid mixture coating layer also contains a conductive agent. Preferably, the conductive agent is a composite conductive agent. More preferably, the composite conductive agent comprises carbon nanotubes and Super P conductive carbon black in a mass ratio of 1:1 to 1:3.
[0011] In a second aspect, the present invention provides a method for preparing a composite negative electrode material as described in any of the foregoing embodiments, comprising: Surface oxidation modification is performed on self-exothermic resin-based hard carbon preforms to introduce oxygen-containing functional groups on their surface. The modified self-exothermic resin-based hard carbon particles, partially neutralized polyacrylic acid mixture, conductive agent, and water were mixed to obtain a slurry, and the pH of the slurry was controlled at 4.5~5.5. The slurry is dried and cured.
[0012] In an optional embodiment, the mass ratio of the self-exothermic resin-based hard carbon particles, the partially neutralized polyacrylic acid mixture, and the conductive agent is (85~92):(4~8):(4~8).
[0013] In an optional embodiment, the drying and curing process includes a low-temperature atmospheric pressure spreading stage and a high-temperature vacuum curing stage. The process conditions for the low-temperature atmospheric pressure spreading stage are: temperature 40~50℃ and drying time 30~60min under atmospheric pressure. The process conditions for the high-temperature vacuum curing stage are: vacuum degree -0.08~-0.095MPa, temperature 110~120℃ and drying time 30~60min. Preferably, a dehydration stage is provided between the low-temperature atmospheric pressure spreading stage and the high-temperature vacuum curing stage. The process conditions for the dehydration stage are: vacuum degree -0.08~-0.095MPa, temperature 70~80℃, and drying time 60~120min.
[0014] Thirdly, the present invention also provides a negative electrode sheet, which includes a current collector and an active coating on the surface of the current collector, the active coating comprising a composite negative electrode material as described in any of the foregoing embodiments.
[0015] Fourthly, the present invention also provides a method for preparing the above-mentioned negative electrode sheet, which includes: coating the slurry in the aforementioned embodiments onto the surface of the current collector, controlling the positive and negative electrode capacity ratio N / P to be 0.8~1.0 according to the lean negative electrode design standard, and controlling the corresponding negative electrode areal density to be 8~12 mg / cm², and then drying and curing according to the drying and curing process of the aforementioned embodiments.
[0016] Preferably, after drying and curing, the product is subjected to rolling, punching and cutting, and shaping heat treatment in sequence. The shaping heat treatment is performed under vacuum of -0.09 to -0.1 MPa and heat treatment at 115 to 125°C for 6 to 48 hours.
[0017] Fifthly, the present invention also provides a sodium-ion battery comprising a negative electrode as described in the foregoing embodiments.
[0018] This invention offers the following advantages: By selecting specific resin-based hard carbon particles and coating their surfaces with a partially neutralized polyacrylic acid mixture, a functionally graded composite interface layer is constructed that combines hydrogen bond anchoring near the carbon matrix with sodium-affinity ionic crosslinking on the far matrix side. This structure achieves tight interfacial bonding primarily through hydrogen bonds on the near-carbon matrix side, significantly enhancing the interfacial mechanical strength. On the far matrix side (electrolyte interface side), an ionic crosslinking network structure dominates, imparting excellent flexible buffering properties to the interface. Simultaneously, the partially neutralized sodium carboxylate groups (-COONa) provide excellent sodium affinity, while the oxygen-containing functional groups introduced through oxidation of the hard carbon surface ensure good wettability to water-based slurries and provide sufficient sites for hydrogen bond anchoring with the coating layer, thereby synergistically optimizing the electrode structure stability and electrochemical compatibility. Under lean anode battery operating conditions, when the sodium storage sites on the hard carbon are close to saturation, the lone pair electrons of the carbonyl oxygen atoms in the neutralized polyacrylic acid molecules at the interface can coordinate with sodium ions in the electrolyte, homogenizing ion transport sites and alleviating concentration polarization. This mechanism significantly reduces the overpotential for sodium metal nucleation. Simultaneously, the ion cross-linking network structure in the coating layer effectively buffers volume deformation during electrodeposition, thereby mitigating cell expansion. This combined function significantly improves the battery's cycle life. Therefore, this invention innovatively extends the role of partially neutralized polyacrylic acid from a traditional binder to a multifunctional interface modification layer for lean anode systems. Its carboxyl groups not only maintain the bonding stability of the electrode structure but, more importantly, enable precise control of sodium ion behavior in the electrolyte system. This design effectively alleviates key scientific problems faced by traditional hard carbon anodes, such as large expansion, poor cycle stability, dendrite growth, and rapid capacity decay, providing an innovative solution for the uniform deposition of sodium metal in lean anode systems. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0020] Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible subranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed subranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.
[0021] In the description of this invention, the terms "comprising," "including," etc., mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships may exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single or multiple.
[0022] The following provides a detailed description of a composite negative electrode material and its preparation method, a negative electrode sheet and its preparation method, and a sodium-ion battery provided by the present invention.
[0023] Some embodiments of the present invention provide a composite anode material comprising a hard carbon matrix and a partially neutralized polyacrylic acid mixture coating layer on the surface of the hard carbon matrix. The partially neutralized polyacrylic acid mixture coating layer is a functional composite layer, primarily exhibiting hydrogen bond anchoring near the hard carbon matrix and primarily exhibiting sodium-affinity ion crosslinking network function away from the hard carbon matrix. The hard carbon matrix is composed of self-exothermic resin-based hard carbon particles. Through the synergistic design of the self-exothermic resin-based hard carbon particles and the partially neutralized polyacrylic acid mixture coating layer, a composite interface layer with both hydrogen bond anchoring and ion crosslinking buffering properties is constructed on the hard carbon surface. This interface layer enhances the interfacial bonding strength through hydrogen bonding, effectively buffering the volume expansion of the hard carbon when storing sodium. Simultaneously, the coordination of carbonyl oxygen in the molecule with sodium ions induces uniform nucleation and deposition of sodium metal, inhibiting dendrite growth. Furthermore, the interfacial passivation reduces the probability of side reactions between the active material and the electrolyte. This multi-dimensional synergistic mechanism significantly improves the cycle life of sodium-ion batteries.
[0024] Self-exothermic resin-based hard carbon particles refer to resin-based hard carbon particles prepared using a self-exothermic crosslinking resin as a precursor. Using these particles as the hard carbon matrix, the self-exothermic resin undergoes a full condensation crosslinking exothermic reaction during curing, forming a high-density three-dimensional resin network. After high-temperature carbonization, this network transforms into a continuous carbon skeleton with a dense structure, few defects, and uniform internal pores. After the condensation reaction consumes some active functional groups, a suitable amount of unreacted active sites remain on the carbon matrix surface, allowing for a gentler and more uniform subsequent air oxidation pretreatment process, preventing excessive etching of the carbon matrix, and stably introducing sufficient oxygen-containing functional groups. These oxygen-containing functional groups can form hydrogen bond anchoring synergistic effects with part of the neutralized polyacrylic acid mixture coating layer, providing a basic carrier for the multifunctional coating interface. During charging and discharging, this multi-point anchoring network efficiently dissipates volumetric deformation stress using the dynamic fracture-reconstruction characteristics of hydrogen bonds, preventing interface debonding and avoiding the rigid structure from breaking, thus synergistically achieving structural stability and flexible buffering. If replaced with ordinary resin that has no obvious exothermic effect, the skeleton is not uniform after carbonization and the surface active sites are unevenly distributed. This makes it impossible to controllably introduce uniform and sufficient oxygen-containing functional groups during subsequent air oxidation. The coating layer lacks sufficient hydrogen bond anchoring sites and is difficult to form a strong interfacial bond with the carbon matrix. Its multiple functions, such as interface passivation, ion flux regulation and sodium deposition guidance, cannot be fully utilized and can only play a limited role in bonding and buffering.
[0025] By constructing a functional composite interface layer on the surface of the hard carbon particles, this interface integrates two sides: one near the carbon matrix, primarily anchored by hydrogen bonds, firmly adhering to the hard carbon surface and enhancing interfacial bonding strength; and the other side away from the matrix, facing the electrolyte, primarily composed of an ion-crosslinked network structure, endowing the interface with flexible buffering capacity, good interfacial wettability, and sodium affinity, thus balancing electrode structural stability and electrochemical reaction compatibility. Under the condition of a lean negative electrode battery, after the sodium storage sites on the hard carbon approach saturation, the carbonyl oxygen atoms in the interface molecules possess lone pairs of electrons, which can form coordination interactions with sodium ions in the electrolyte, effectively reducing the overpotential for sodium metal nucleation. The uniformly distributed sodium-affinity active sites at the interface can balance the sodium ion flux, guiding sodium metal to uniformly nucleate and deposit on the surface and between the hard carbon particles; simultaneously, the three-dimensional crosslinked network can buffer the volume deformation generated during the deposition process, and the interfacial passivation effect reduces the probability of side reactions between the active material and the electrolyte, inhibits sodium dendrite formation, and improves battery cycle life and safety.
[0026] Specifically, in order to form an integrated composite interface that combines hydrogen bond anchoring points and ionic cross-linking networks, the degree of neutralization of the partially neutralized polyacrylic acid mixture in the partially neutralized polyacrylic acid mixture coating layer is 30-70%, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%.
[0027] In some embodiments, the partially neutralized polyacrylic acid mixture coating layer also contains a conductive agent. Preferably, the conductive agent is a composite conductive agent; more preferably, the composite conductive agent includes carbon nanotubes and Super P conductive carbon black in a mass ratio of 1:1 to 1:3. The partially neutralized polyacrylic acid mixture coating layer has poor conductivity. The addition of the conductive agent can build a three-dimensional point-contact conductive network within it, significantly improving the electron conduction rate of a single particle, resulting in a decrease in the overall impedance of the electrode and an improvement in rate performance. The Super P conductive carbon black fills the gaps in the material, working synergistically with the carbon nanotubes to form a through-pore channel, accelerating sodium ion diffusion; the flexible ion-crosslinked network acts as a volume stress buffer, and the conductive agent provides a conductive framework support.
[0028] Some embodiments of the present invention also provide a negative electrode sheet, which includes a current collector and an active coating on the surface of the current collector, the active coating comprising a composite negative electrode material as described in any of the foregoing embodiments.
[0029] Some embodiments of the present invention also provide a sodium-ion battery comprising the negative electrode sheet as described in the foregoing embodiments.
[0030] Some embodiments of the present invention also provide a method for preparing a composite negative electrode material as described in any of the foregoing embodiments, comprising: Surface oxidation modification is performed on self-exothermic resin-based hard carbon preforms to introduce oxygen-containing functional groups on their surface. The modified self-exothermic resin-based hard carbon particles, partially neutralized polyacrylic acid mixture, conductive agent, and water were mixed to obtain a slurry, and the pH of the slurry was controlled at 4.5~5.5. The slurry is dried and cured.
[0031] It should be noted that some embodiments of the present invention also provide a method for preparing the above-mentioned negative electrode sheet, which includes: coating the slurry in the aforementioned embodiments onto the surface of the current collector, controlling the positive and negative electrode capacity ratio N / P to be 0.8~1.0 according to the lean negative electrode design standard, and controlling the corresponding negative electrode areal density to be 8~12 mg / cm², and then drying and curing according to the drying and curing process of the aforementioned embodiments.
[0032] Specifically, in some embodiments, the preparation process of sodium-ion battery cells is used to uniformly describe the preparation technology and conditions of negative electrode materials, negative electrode sheets, and sodium-ion battery cells, which includes the following steps: S1. Preparation of self-exothermic resin-based hard carbon particles.
[0033] (1) Selection of precursor raw materials.
[0034] Specifically, the precursor of self-exothermic resin-based hard carbon particles is a self-exothermic resin whose molecular chain carries at least one functional group selected from hydroxyl, carboxyl, cyano, and hydroxymethyl groups. This self-exothermic resin undergoes an exothermic condensation-crosslinking reaction during pyrolysis. Within the crosslinking and curing temperature range of 200–400°C, the heat released by the functional group condensation promotes uniform crosslinking and molding of the resin matrix, constructing a dense carbon skeleton with fewer defects and optimizing the internal pore structure of the hard carbon.
[0035] The above-mentioned resin powder must pass through a 100-mesh standard sieve. Its thermal condensation exothermic characteristics are as follows: under an inert atmosphere with a heating rate of 5-10℃ / min, a significant exothermic peak appears in the 200-400℃ range, with an integrated exothermic heat of not less than 10 J / g. This exothermic reaction mainly originates from the condensation crosslinking reaction of hydroxyl, hydroxymethyl, and carboxyl groups; the cyano group participates in the cyclization polymerization to assist in the exothermic reaction. This characteristic can be confirmed by differential scanning calorimetry (DSC) testing of commercially available raw materials.
[0036] (2) Pre-carbonization treatment.
[0037] The sieved resin powder is placed inside a tube furnace, and nitrogen or argon inert protective gas is introduced; the temperature is increased to 200-400℃ at a rate of 0.5-2℃ / min, and held for 1-2 hours. During this stage, the resin functional groups undergo an exothermic condensation reaction, uniformly cross-linking and forming a preliminary stable carbon skeleton; slow heating can ensure uniform cross-linking.
[0038] (3) High-temperature carbonization and shaping.
[0039] After the pre-carbonization process is completed, while maintaining the inert atmosphere, the temperature is increased to 800-1200℃ at a heating rate of 2-5℃ / min and held for 2-4 hours to complete the crystal form and pore shape of the carbon material. After the holding period, the material is allowed to cool naturally to room temperature to obtain the basic hard carbon blank.
[0040] (4) After crushing the basic hard carbon blank, pass it through a 200-mesh sieve. Place the powder in a muffle furnace and oxidize it at 250-280℃ for 0.5-1h in an air atmosphere. The preferred process parameters are 260℃ for 45min, which smoothly introduces hydroxyl and carboxyl oxygen-containing functional groups onto the surface of the carbon material. Oxygen molecules in the air are first adsorbed onto the surface of the carbon material. Driven by heat energy, they react with surface active carbon atoms. Some carbon skeletons are preferentially oxidized. As the degree of oxidation deepens, the functional groups are oxidized from alcohol / phenol hydroxyl (-OH) and ether / epoxy (-COC-) to carbonyl (-C=O) and carboxyl (-COOH). High-temperature heat treatment can effectively increase the surface oxygen content. Heat treatment at 260℃ for 45min can provide the activation energy required for the oxidation reaction without damaging the material itself, ensuring that the material has enough time to react, and not causing the generated functional groups to decompose in large quantities due to the long time.
[0041] Finished product specifications: XPS test shows surface oxygen functional group content of 2~5 at.%, BET test shows specific surface area of 100~250 m² / g.
[0042] It should be noted that the high-temperature carbonization temperature can be adjusted as needed within the range of 1000~1400℃; the resin precursor can be a commercially available phenolic resin micro powder that meets the DSC exothermic requirements, without the need for self-synthesis.
[0043] S2, Preparation of negative electrode slurry.
[0044] The slurry composition includes modified self-exothermic resin-based hard carbon particles, partially neutralized polyacrylic acid mixture, composite conductive agent, deionized water and pH adjuster; the mass ratio of self-exothermic resin-based hard carbon particles, partially neutralized polyacrylic acid mixture and conductive agent is (85~92):(4~8):(4~8).
[0045] Material specifications: Modified hard carbon: Surface oxygen-containing functional groups meet standards, providing hydrogen bond anchoring sites for the binder; Partially neutralized polyacrylic acid mixture: Polyacrylic acid and sodium polyacrylate are compounded, with an overall neutralization degree of 30-70%. Free carboxyl groups are used for interfacial anchoring, and carboxylate ions ensure ion conductivity; The pH of the solution is adjusted to 4.5-5.5 using a dilute sodium hydroxide solution and a precision pH meter; Composite conductive agent: Carbon nanotubes and Super P are compounded at a mass ratio of 1:1 to 1:3 to form a continuous conductive network; Deionized water is used as the solvent; 0.1-1 mol / L dilute sodium hydroxide solution is used as the pH adjuster.
[0046] In some embodiments, the preparation of the negative electrode slurry includes the following steps: selecting a partially neutralized polyacrylic acid mixture with a viscosity-average molecular weight of 300k~500k, controlling the overall neutralization degree to 40~60%, adding it to deionized water at 60℃, stirring at 300rpm to dissolve, and preparing a binder mother liquor with a mass fraction of 5~8wt%; adding carbon nanotubes and Super P composite conductive agent to the binder mother liquor according to the formula, dispersing at high speed at 2000~3000rpm for 30min to form a uniform conductive colloid; slowly adding self-exothermic resin-based hard carbon particles to the colloid in batches, with a batch addition interval of 5min; adding deionized water to adjust the slurry solid content to 35~45%, and stirring continuously for 1h; then transferring the slurry to a vacuum stirring device, stirring under a negative pressure of -0.08~-0.1MPa for 20~30min to completely eliminate internal air bubbles.
[0047] It should be noted that in some other embodiments, the neutralization degree can be maintained by fixing the 1:1 ratio of PAA to sodium polyacrylate, thereby reducing the pH adjustment operation; the conductive agent can be any type of Super P, carbon nanotube, or graphene; the solid content of the slurry can be reasonably adjusted in the range of 30-50%.
[0048] S3, electrode coating and segmented vacuum drying.
[0049] Specifically, the coating process is as follows: the prepared slurry is uniformly coated onto the surface of a 10~12μm carbon-coated aluminum foil current collector using a transfer coating machine; according to the lean negative electrode design standard, the positive and negative electrode capacity ratio N / P is controlled at 0.8~1.0, and the corresponding negative electrode areal density is controlled at 8~12mg / cm².
[0050] The segmented vacuum drying process includes: Low-temperature and atmospheric-pressure spreading stage: Under atmospheric pressure, the temperature is 40~50℃ and the drying time is 30~60min; during this stage, the moisture evaporates at a low speed, the PAA molecular chains fully extend, and uniformly coat the hard carbon particles.
[0051] Dehydration stage: vacuum degree -0.08~-0.095MPa, temperature 70~80℃, drying time 60~120min. This stage removes most of the free water, and the carboxyl groups form hydrogen bonds with the hydroxyl groups on the hard carbon surface, completing the shaping of the inner anchoring structure.
[0052] High-temperature vacuum curing stage: vacuum degree -0.08~-0.095MPa, temperature 110~120℃, drying time 30~60min; this stage thoroughly removes residual trace moisture, promotes the rearrangement and fixation of some neutralized carboxyl / sodium carboxylate groups on the polyacrylic acid molecular chain, forming an ion-associated network in the dry state. This ion-associated network partially transforms into a dynamic ion-conducting interface after subsequent liquid injection, with carboxylate anions anchored on the polymer chain, regulating sodium ion flux through electrostatic repulsion, and synergistically inhibiting dendrite growth.
[0053] S4, electrode rolling, cutting and vacuum heat treatment.
[0054] (1) Roller pressing: After drying, the electrode is naturally cooled and compacted using roller pressing equipment. The compaction density of the electrode is controlled at 1.0~1.1 g / cm³ to balance the porosity and stability of the structure.
[0055] (2) Punching and cutting: According to the battery design dimensions, use a mold to punch and cut the negative electrode sheet with uniform specifications.
[0056] (3) Shaping heat treatment: The electrode is placed in a vacuum oven and kept at -0.1MPa vacuum and 120℃ for 12~24h, preferably 18h; to promote the reconstruction and arrangement of PAA molecular chains, increase the proportion of active carboxyl groups on the electrode surface, and release the internal stress generated by rolling.
[0057] It should be noted that the heat treatment time can be adjusted in the range of 6 to 48 hours, with the interface modification effect being optimal in the range of 12 to 24 hours.
[0058] S5, sodium-ion battery cell assembly.
[0059] The prepared electrode, polyanionic positive electrode Na3V2(PO4)3, and PP-based separator were matched and assembled into a soft-pack battery. The electrolyte system used diethylene glycol dimethyl ether solvent to dissolve 1 mol / L NaPF6, and an additional 5% volume fraction of FEC additive was added to optimize the interface SEI film characteristics and improve the compatibility between the electrolyte and the coating layer.
[0060] Based on the above process, it can be seen that by selecting phenolic resin powder with exothermic thermal condensation properties as raw material, and through segmented carbonization combined with controlled air oxidation, a modified hard carbon material with a uniform framework and a surface rich in oxygen-containing active functional groups is prepared. The modified hard carbon is then mixed with a mixture of neutralized polyacrylic acid, a composite conductive agent, and deionized water in a specific ratio, with strict control over the feeding sequence and slurry pH. After three-stage segmented vacuum drying, a firm anchoring is achieved at the hard carbon-coating interface via hydrogen bonds. The overall ion cross-linked network of the coating layer provides sodium affinity, buffering, and sodium ion regulation functions. Subsequent rolling and shaping heat treatment optimize the electrode density and interfacial functional group distribution, ultimately assembling a sodium-ion battery with a lean negative electrode. Uniform sodium ion deposition is achieved through interfacial synergy, resulting in high capacity, low expansion, and long cycle life, achieving comprehensive electrochemical performance.
[0061] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0062] Example 1 This embodiment provides a method for preparing a negative electrode composite material, a corresponding negative electrode sheet, and a sodium-ion battery cell, which includes the following steps: (1) The Fujian Tianli thermosetting phenolic resin that meets the DSC conditions is ground and passed through a 100-mesh standard sieve. The resulting resin powder is placed inside a tube furnace and inert protective gas of nitrogen or argon is introduced. The temperature is increased to 300℃ at a rate of 1℃ / min and held for 1.5h. The inert atmosphere is kept constant and the temperature is increased to 1000℃ at a rate of 3℃ / min and held for 3h. The resulting basic hard carbon blank is then crushed and passed through a 200-mesh sieve. The powder is placed in a muffle furnace and oxidized at 260℃ for 45min in an air atmosphere to obtain modified self-exothermic resin-based hard carbon particles. XPS analysis shows that the oxygen functional group content on the surface is 3.8 at.%, and BET analysis shows that the specific surface area is 190 m² / g.
[0063] (2) Select a partially neutralized polyacrylic acid mixture (polyacrylic acid and sodium polyacrylate) with a viscosity-average molecular weight of 400k, control the overall neutralization degree to 50%, put it into deionized water at 60℃, stir and dissolve at 300rpm, and prepare a 6 wt% binder mother liquor; add carbon nanotube and Super P composite conductive agent to the binder mother liquor according to the ratio, disperse at 2500rpm for 30min to form a uniform conductive colloid; slowly add self-exothermic resin-based hard carbon particles to the colloid in batches, with a batch addition interval of 5min; add deionized water to adjust the slurry solid content to 40%, and continue stirring for 1h; then transfer the slurry to a vacuum stirring device, stir under a negative pressure of -0.09MPa for 25min to completely eliminate internal bubbles.
[0064] The solution pH was adjusted to 4.5 using a 0.5 mol / L dilute sodium hydroxide solution and a precision pH meter; the composite conductive agent was a mixture of carbon nanotubes and Super P in a mass ratio of 1:2; the mass ratio of hard carbon particles, partially neutralized polyacrylic acid mixture, and conductive agent was 88:6:6.
[0065] (3) The prepared slurry was uniformly coated on the surface of the 11μm carbon-coated aluminum foil current collector using a transfer coating machine; according to the lean negative electrode design standard, the positive and negative electrode capacity ratio N / P was controlled to be 0.8, and the corresponding negative electrode surface density was controlled to be 10 mg / cm².
[0066] (4) A segmented vacuum drying process is adopted for drying, which includes: Low-temperature and atmospheric-pressure spreading stage: Under atmospheric pressure, the temperature is 45℃ and the drying time is 45min; Dehydration stage: vacuum degree -0.09MPa, temperature 75℃, drying time 90 min; High-temperature vacuum curing stage: vacuum degree -0.09MPa, temperature 115℃, drying time 45 min.
[0067] (5) After drying, the electrode sheets are naturally cooled and compacted using a roller press to control the compaction density of the electrode sheets to 1.05 g / cm³.
[0068] (6) According to the battery design dimensions, use a mold to punch and cut the negative electrode sheet with uniform specifications.
[0069] (7) Place the electrode in a vacuum oven and keep it at -0.1MPa vacuum and 120℃ for 18 hours.
[0070] (8) The prepared negative electrode, polyanionic positive electrode Na3V2(PO4)3, and PP-based separator are matched and assembled into a soft-pack battery; the electrolyte system uses diethylene glycol dimethyl ether solvent to dissolve 1 mol / L NaPF6, and an additional 5% volume fraction of FEC additive is added.
[0071] Example 2 The only difference between this embodiment and Example 1 is that the modified self-exothermic resin-based hard carbon particles were obtained by oxidation treatment at 200°C for 75 minutes in an air atmosphere. XPS analysis showed that the oxygen functional group content on the surface was 2.3 at.%, and BET analysis showed that the specific surface area was 115 m² / g. All other process parameters and material ratios remained the same as in Example 1.
[0072] Example 3 The only difference between this embodiment and embodiment 1 is that the overall neutralization degree of the polyacrylic acid mixture in step (2) is adjusted to 30%; all other process parameters and material ratios are consistent with those in embodiment 1.
[0073] Example 4 The only difference between this embodiment and Example 1 is that in step (2), the mass ratio of polyacrylic acid to sodium polyacrylate is fixed at 1:1.3 (neutralization degree of about 50%), and pH adjustment is not used.
[0074] Example 5 The only difference between this embodiment and Embodiment 1 is that the segmented vacuum drying process in step (4) only includes: Low-temperature and atmospheric-pressure spreading stage: Under atmospheric pressure, the temperature is 45℃ and the drying time is 45 min; High-temperature vacuum curing stage: vacuum degree -0.09MPa, temperature 115℃, drying time 135min. All other process parameters and material ratios are consistent with those in Example 1.
[0075] Comparative Example 1 The difference between this comparative example and Example 1 is that in steps (2) to (8), commercially available ordinary resin-based hard carbon is used directly to replace the modified self-exothermic resin-based hard carbon particles prepared in step (1) of Example 1. The ordinary hard carbon used is Baisige NHC-330-5 hard carbon (resin-based hard carbon). DSC detection showed that its integral exothermic heat in the range of 200~400℃ had no obvious exothermic peak, indicating that the resin lacks condensation crosslinking exothermic characteristics. The hard carbon matrix was subjected to air oxidation at 260℃ for 45min in the same manner as in Example 1. The remaining material ratios, slurry preparation, coating, drying, rolling, heat treatment, and cell assembly process parameters are completely consistent with those in Example 1. Ordinary hard carbon has a loose skeleton and many structural defects. Under the same oxidation conditions, it is easy to over-etch at the defect sites. Some newly formed pores collapse and close due to insufficient skeleton support. After the oxidation treatment in step (1) of this comparative example, the content of oxygen-containing functional groups on the surface of the ordinary hard carbon particles by XPS detection is only 1.2 at.%, and the specific surface area by BET test is 135 m² / g, which is significantly lower than the 3.8 at.% and 190 m² / g of the self-exothermic resin-based hard carbon in Example 1.
[0076] Comparative Example 2 The only difference between this comparative example and Example 1 is that no oxidation treatment is performed in step (1).
[0077] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step (2), pure polyacrylic acid with a viscosity-average molecular weight of 400k is used to replace part of the neutralized polyacrylic acid mixture in Example 1. This comparative example does not add a pH adjuster, and the system does not contain pre-mixed sodium polyacrylate to avoid in-situ neutralization by introducing alkali; the remaining material ratios, coating, drying, rolling, heat treatment, and cell assembly process parameters are completely consistent with those of Example 1.
[0078] The electrochemical performance of the lean negative electrode cells prepared above was tested, and the results are shown in Table 1.
[0079] Table 1
[0080] Comparing Example 2 with Example 1: The only difference between the two is the oxidation conditions. The oxidation conditions are milder, the overall activation effect is weaker, and there are fewer micropores. This results in a low content of oxygen-containing functional groups in hard carbon, a small specific surface area, and fewer interfacial anchoring sites. As a result, the nucleation overpotential increases, the capacity retention rate decreases, and the cell expansion increases slightly, making the performance inferior to Example 1.
[0081] Comparing Example 3 with Example 1: The neutralization degree of the binder decreased to 30%. The decrease in neutralization degree means that there are more carboxyl groups and fewer sodium ions, which hinders ion conduction, increases the nucleation overpotential, reduces the cycle capacity retention rate, and exacerbates cell expansion.
[0082] Comparing Example 4 with Example 1: In-situ pH control was eliminated, and polyacrylic acid and sodium polyacrylate were physically blended in a 1:1 ratio. The carboxylate groups were prone to local aggregation, the regularity of the interfacial hydrogen bond and ion crosslinking arrangement decreased, the sodium ion transport and interfacial anchoring effects were weakened, and the various properties declined slightly. Comparing Example 5 with Example 1: The low-temperature dehydration section was omitted, resulting in the hydrogen bond anchoring structure not being fully stabilized; rapid solvent evaporation caused the binder to agglomerate, the interfacial bonding force decreased, the nucleation overpotential increased significantly, the cycle stability decreased significantly, and the cell expansion increased significantly. Comparing Comparative Example 1 with Example 1: Commercially available ordinary hard carbon was used. The hard carbon matrix has disordered pores, many defects, uneven oxidation, and the surface oxygen-containing functional groups are far lower than those in Example 1. The hydrogen bond anchoring points are seriously insufficient, resulting in a significant deterioration in performance. It can be seen that the dense and uniform carbon skeleton formed by the self-exothermic resin is crucial for ensuring cycle stability and suppressing cell expansion.
[0083] Comparing Comparative Example 2 with Example 1: Hard carbon was not oxidized by air, and the surface lacked oxygen-containing functional groups. During cycling, the coating layer and the substrate were prone to local detachment, resulting in poor interface stability, increased nucleation overpotential, and significantly aggravated capacity decay and cell expansion. It can be seen that oxidation modification can reduce nucleation overpotential to a certain extent, which is beneficial to the cell's electrical performance.
[0084] Comparing Comparative Example 3 with Example 1: The binder is pure unneutralized polyacrylic acid, which has no ionized carboxylate sites. The sodium ion interface coordination is missing, making it difficult to control sodium deposition. The nucleation overpotential and cell expansion are the highest among all groups, the cycle capacity retention rate is the lowest, the electrode interface is extremely prone to failure, and the electrochemical performance is the worst.
[0085] In summary, the optimal process scheme is Example 1: self-exothermic phenolic resin hard carbon + 50% neutralized PAA, precise in-situ neutralization control with dilute alkali + three-stage vacuum drying process including low-temperature dehydration. This results in continuous and uniform interfacial hydrogen bond anchoring, the lowest sodium deposition resistance, optimal cycle stability, and minimal cell expansion. Simplifications such as replacing the modified resin, lowering the binder neutralization, eliminating precise pH control, and omitting the low-temperature dehydration stage will progressively weaken the interfacial anchoring effect and decrease electrochemical performance.
[0086] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A composite negative electrode material, characterized in that, It includes a hard carbon matrix and a partially neutralized polyacrylic acid mixture coating layer covering the surface of the hard carbon matrix. The partially neutralized polyacrylic acid mixture coating layer is a functional composite layer, which mainly functions as hydrogen bond anchoring on the side close to the hard carbon matrix and mainly functions as sodium affinity of ion crosslinking network on the side away from the hard carbon matrix. The hard carbon matrix is a self-exothermic resin-based hard carbon particle.
2. The composite negative electrode material according to claim 1, characterized in that, The precursor of the self-exothermic resin-based hard carbon particles is a self-exothermic resin whose molecular chain carries at least one functional group among hydroxyl, carboxyl, cyano, and hydroxymethyl groups. The self-exothermic resin can undergo a condensation crosslinking exothermic reaction during pyrolysis. Preferably, the surface oxygen-containing functional group content of the self-exothermic resin-based hard carbon particles is 2~5 at.%, and the specific surface area is 100~250 m² / g.
3. The composite negative electrode material according to claim 1, characterized in that, The degree of neutralization of the partially neutralized polyacrylic acid mixture forming the partially neutralized polyacrylic acid mixture coating layer is 30-70%.
4. The composite negative electrode material according to any one of claims 1 to 3, characterized in that, The partially neutralized polyacrylic acid mixture coating layer also contains a conductive agent. Preferably, the conductive agent is a composite conductive agent. More preferably, the composite conductive agent includes carbon nanotubes and Super P conductive carbon black in a mass ratio of 1:1 to 1:
3.
5. A method for preparing the composite negative electrode material according to any one of claims 1 to 4, characterized in that, It includes: The surface of self-exothermic resin-based hard carbon particles is modified by oxidation to introduce oxygen-containing functional groups on their surface. The modified self-exothermic resin-based hard carbon particles, partially neutralized polyacrylic acid mixture, conductive agent, and water were mixed to obtain a slurry, and the pH of the slurry was controlled at 4.5~5.
5. The slurry is dried and cured.
6. The method for preparing the composite negative electrode material according to claim 5, characterized in that, The mass ratio of the self-exothermic resin-based hard carbon particles, the partially neutralized polyacrylic acid mixture, and the conductive agent is (85~92):(4~8):(4~8).
7. The method for preparing the composite negative electrode material according to claim 5, characterized in that, The drying and curing process includes a low-temperature atmospheric pressure spreading stage and a high-temperature vacuum curing stage. The process conditions for the low-temperature atmospheric pressure spreading stage are: temperature 40~50℃ and drying time 30~60min under atmospheric pressure. The process conditions for the high-temperature vacuum curing stage are: vacuum degree -0.08~-0.095MPa, temperature 110~120℃ and drying time 30~60min. Preferably, a dehydration stage is provided between the low-temperature atmospheric pressure spreading stage and the high-temperature vacuum curing stage. The process conditions for the dehydration stage are: vacuum degree -0.08~-0.095MPa, temperature 70~80℃, and drying time 60~120min.
8. A negative electrode sheet, characterized in that, It includes a current collector and an active coating on the surface of the current collector, the active coating including the composite negative electrode material as described in any one of claims 1 to 4.
9. A method for preparing a negative electrode sheet as described in claim 8, characterized in that, It includes: The slurry as described in claim 5 is coated on the surface of the current collector. According to the lean negative electrode design standard, the positive and negative electrode capacity ratio N / P is controlled to be 0.8~1.0, and the corresponding negative electrode surface density is controlled to be 8~12 mg / cm². Then, the slurry is dried and cured according to the drying and curing process described in claim 7. Preferably, after drying and curing, the product is subjected to rolling, punching and cutting, and shaping heat treatment in sequence. The shaping heat treatment is performed under vacuum of -0.09 to -0.1 MPa and heat treatment at 115 to 125°C for 6 to 48 hours.
10. A sodium-ion battery, characterized in that, It includes the negative electrode as described in claim 8.